PENGEMBANGAN KONTEN SIPEJAR MANAJEMEN LEMBAGA INFORMASI BERBASIS INKLUSI SOSIAL UNTUK MAHASISWA ILMU PERPUSTAKAAN - Inawati, Inawati; Setiawan, setiawan; Moh. Safii (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2024)
Microlearning-based learning content is a form of innovation that needs to be carried out to answer current challenges. Microlearning is a method of creating learning content into small, focused parts with the help of information technology. The content is usually created in the form of explanatory videos, motion graphics and infographics. This research aims to develop SIPEJAR content based on microlearning for Information Institution Management courses based on social inclusion for library science students. The research method applied in this study uses an applied research approach with the aim of overcoming practical problems or producing new product innovations that can be implemented directly. The findings from this applied research have practical application, and one of the approaches is the research and development method. This approach is used to produce concrete solutions that can provide direct benefits for practitioners, and has the potential to present innovative products as a result of the exploration and development carried out. Research results. Evaluation results by experts show that the overall validity of the media reached a score of 84 with an average value of 3.84 from a maximum score of 88. With a percentage of 95.45%, this media is categorized as very high and is considered suitable as an effective learning tool. Material validation by validators also gave positive results, with a total score of 52, an average of 3.55, and a percentage of 86.67%, indicating the validity of the material elements in the learning product. Furthermore, the design validation results showed an overall score of 78, an average of 3.91, and a percentage 97.50% (very valid), indicating that the product design is considered very valid and suitable for use in the context of library management learning. Product trials on students also produced positive numbers, with a total of 86.8, an average of 3.48, and a percentage of 86.84%, indicating that the product is suitable for use in the learning process, making a positive contribution to students' understanding of library management. Overall, this research confirms that the evaluated learning products are of high quality and can be relied upon as effective learning tools in the context of library management.